OTORITAS IBADAH OLEH PEMERINTAH: SOLUSI PROBLEM PENETAPAN AWAL RAMADHAN DAN SYAWAL - Muslich Shabir; Mu’ammar Mu’ammar (Jurnal Ilmiah Ibtida: Jurnal Prodi PGMI STIT Pemalang, 2022)
Abstract Government authorities to set the beginning of Ramadan and Shawwal towards uniformity and binding decisions continue to be pursued. This can be seen from the representation of invitations present at the congregation's congregation, which made the atmosphere of the congregation feel dynamic with various methods and data presented by each group. In this context, this paper will explore the roots of the differences in the early methods of Ramadan and Shawwal, make a comparison of the results of reckoning and ru'yah and offer alternative solutions related to the authority of worship and the possibility of determination through jurisprudence. The government-owned authority must be a supremacy of the law which exceeds other authorities, both traditional, personal and legal rational authorities. As the holder of formal legal authority and has the highest hierarchy in the political system, the government has demonstrated its authority in issuing a number of decisions related to worship. As for the special beginning of Ramadhan and the Syawal of the decision on the results of the trial of itsbat which are then stipulated by the Minister of Religion as the government, then the other authorities should not be entitled anymore, except in the ikhbar level.